1998
DOI: 10.1002/pc.10119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interfacial interactions on the properties of PVC/cellulosic fiber composites

Abstract: The surface properties at the interface between thermoplastic and cellulosic fibers strongly influence the mechanical properties of plastic/cellulosic fiber composites. This paper examines the role of surface acid‐base properties of plasticized PVC and cellulosic fibers on the mechanical properties of the composites. The acid‐base surface characteristics of cellulosic fibers were modified by treating the fibers with γ‐aminopropyltriethoxysilane (A‐1100), dichlorodiethylsilane, phthalic anhydride, and maleated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(163 citation statements)
references
References 15 publications
4
150
0
4
Order By: Relevance
“…The organofunctional group is responsible for bonding with the polymer via covalent reaction or physical interaction with other phases. Matuana et al (1998a;1998b) found that the adhesion between PVC and cellulosic fibers was significantly improved with aminosilane. Figure 1 shows a schematic illustration of the possible interface between silane modified cellulose nanocrystals (SCNC) and poly (vinyl chloride) matrix (PVC).…”
Section: Introductionmentioning
confidence: 99%
“…The organofunctional group is responsible for bonding with the polymer via covalent reaction or physical interaction with other phases. Matuana et al (1998a;1998b) found that the adhesion between PVC and cellulosic fibers was significantly improved with aminosilane. Figure 1 shows a schematic illustration of the possible interface between silane modified cellulose nanocrystals (SCNC) and poly (vinyl chloride) matrix (PVC).…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts to overcome the cost of PLA included blending with fillers such as cellulosic fibers [5]. However, the lowered cost due to filler addition is usually achieved at the expense of other properties such as the ductility (lower elongation at break) and lower impact resistance, because the incorporated brittle cellulosic fibers alter the ductile mode of failure of the matrix, making the composites more brittle than neat polymer [6][7][8]. Continuous efforts seek to further reduce the cost of PLA while enhancing its flexibility and toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Também não foi observado uma alteração significativa do módulo de Young com adição da fibra de bananeira não tratada e tratada. Este comportamento pode estar relacionado com o fato do PVC utilizado ser rígido, pois os autores que observaram um aumento significativo do módulo de Young em compósitos de PVC com fibras naturais utilizaram matrizes plastificadas e os valores máximos alcançados nos compósitos obtidos são próximos aos observados neste trabalho [8][9][10][11] com PVC rígido. …”
Section: Resultsunclassified
“…Hoje já são utilizadas fibras de sisal, bambu, bagaço de cana-de-açúcar, curauá, madeira, fibra de bananeira, entre outras. O emprego de fibras naturais como reforço em matriz polimérica, tanto utilizando materiais termofixos como as resinas de poliésteres, epóxis e fenólicas como termoplásticos, principalmente o polipropileno (PP), polietileno (PE) [6,7] e poucos estudos utilizam o poli (cloreto de vinila) (PVC) flexível [8][9][10][11][12][13][14] e rígido [15,16]. Zainudin et al [15] avaliaram a degradação térmica de compósitos de PVC rígido e fibra de bananeira, e foi observado que a adição das fibras não altera o processo de degradação térmica do PVC.…”
Section: Introductionunclassified